The system of systems paradigm to reduce the complexity of data lifecycle management. Case of the security information and event management. (17th December 2019) - Arass, Mohammed El; Ouazzani-Touhami, Khadija; Souissi, Nissrine
Big data management is becoming a challenging mission. Several data lifecycles were proposed to deal with this situation, but neglect cycle management and big data requirements. To fill the gap, the paper introduces the system of systems paradigm to reduce the complexity of cycle management and thereby satisfy big and smart data requirements. This paper demonstrates that the SoS paradigm applied to data lifecycle makes it possible to better organise data at the managerial and operational levels. This demonstration has been proven through a security information event management proof of concept (SIEM POC) use case.